Nanosonosensitizer‐Augmented Sono‐Immunotherapy for Glioblastoma by Non‐Invasive Opening of the Blood–Brain Barrier. (27th November 2022) - Lin, Danmin; Wang, Zhen; Long, Wei; Xu, Mingze; Liu, Aolu; Gao, Yifei; Wen, Zhu; Liu, Chao; He, Jiecheng; Cheng, Yuxue; Jiang, Siyuan; Chen, Jiapeng; et al.
Abstract: The presence of blood–brain barrier (BBB) that limits effective penetration of therapeutics is the main reason for poor outcomes of glioblastoma (GBM) treatment. Ultrasound (US) combined with microbubbles (MBs) can precisely disrupt the tight junctions of brain endothelial cells, thus creating "acoustic pores" and non‐invasive opening the BBB. Here, chitosan oligosaccharide (COS) is conjugated with a sonosensitizer protoporphyrin IX (PpIX) and an immune‐enhancing adjuvant Poly(I:C) via electrostatic adsorption, and cross‐linked with a tumor‐targeting molecule hyaluronic acid (HA) affording nanosonosensitizers HA‐Poly(I:C)/COS‐PpIX (abbreviated as "HP/CP" NSs). HP/CP NSs can target and penetrate GBMs, and trigger reactive oxygen species production upon US, simultaneously causing mitochondrial dysfunction and DNA damage. Tumor‐associated antigens released by sonodynamic therapy‐induced immunogenic cell death and loaded Poly(I:C) form an in situ vaccine together to potentiate antitumor immune responses. In orthotopic GBM mice models, the HP/CP+US treatments prolong mice survival, enhance cytotoxic T‐lymphocytes infiltration, and activate peripheral immune circulation. Besides, HP/CP NSs possess favorable biosafety profiles. Collectively, this study sheds light on the application of HP/CP NSs for synergistic sono‐immunotherapy of GBMs after non‐invasive opening of the BBB. Abstract : Versatile HP/CP nanosonosensitizers (HP/CP NSs) are developed by integrating the sonosensitizer protoporphyrin IX, the immune‐enhancing adjuvant Poly(I:C), and tumor‐targeting molecule hyaluronic acid. After non‐invasive opening of the blood–brain barrier by ultrasoun and microbubbles, the HP/CP NSs target tumors for combined sono/immunotherapy of orthotopic glioblastoma.